The role of frataxin in fission yeast iron metabolism: Implications for Friedreich's ataxia - Wang, Yu; Wang, Yiwei; Marcus, S.; Busenlehner, L.S. (Biochimica et biophysica acta, 2014)
The neurodegenerative disease Friedreich's ataxia is the result of frataxin deficiency. Frataxin is a mitochondrial protein involved in iron–sulfur cluster (Fe–S) cofactor biogenesis, but its functional role in this pathway is debated. This is due to the interconnectivity of iron metabolic and oxidative stress response pathways that make distinguishing primary effects of frataxin deficiency challenging. Since Fe–S cluster assembly is conserved, frataxin overexpression phenotypes in a simple eukaryotic organism will provide additional insight into frataxin function. The Schizosaccharomyces pombe frataxin homologue (fxn1) was overexpressed from a plasmid under a thiamine repressible promoter. The S. pombe transformants were characterized at several expression strengths for cellular growth, mitochondrial organization, iron levels, oxidative stress, and activities of Fe–S cluster containing enzymes. Observed phenotypes were dependent on the amount of Fxn1 overexpression. High Fxn1 overexpression severely inhibited S. pombe growth, impaired mitochondrial membrane integrity and cellular respiration, and led to Fxn1 aggregation. Cellular iron accumulation was observed at moderate Fxn1 overexpression but was most pronounced at high levels of Fxn1. All levels of Fxn1 overexpression up-regulated oxidative stress defense and mitochondrial Fe–S cluster containing enzyme activities. Despite the presence of oxidative stress and accumulated iron, activation of Fe–S cluster enzymes was common to all levels of Fxn1 overexpression; therefore, Fxn1 may regulate the efficiency of Fe–S cluster biogenesis in S. pombe. We provide evidence that suggests that dysregulated Fe–S cluster biogenesis is a primary effect of both frataxin overexpression and deficiency as in Friedreich's ataxia. [Display omitted] •Frataxin plays an unclear role in iron–sulfur cluster biogenesis in mitochondria.•We characterized the phenotype of frataxin overexpression in fission yeast.•Fe–S enzymes had increased activities despite iron overload and oxidative stress.•Frataxin is most likely a regulator of Fe–S biogenesis.